Carrier‐Induced Modification of Palladium Nanoparticles on Porous Boron Nitride for Alkyne Semi‐Hydrogenation. Issue 44 (13th August 2020) - Büchele, Simon; Chen, Zupeng; Fako, Edvin; Krumeich, Frank; Hauert, Roland; Safonova, Olga V.; López, Núria; Mitchell, Sharon; Pérez‐Ramírez, Javier
Abstract: Chemical modifiers enhance the efficiency of metal catalysts in numerous applications, but their introduction often involves toxic or expensive precursors and complicates the synthesis. Here, we show that a porous boron nitride carrier can directly modify supported palladium nanoparticles, originating unparalleled performance in the continuous semi‐hydrogenation of alkynes. Analysis of the impact of various structural parameters reveals that using a defective high surface area boron nitride and ensuring a palladium particle size of 4–5 nm is critical for maximizing the specific rate. The combined experimental and theoretical analyses point towards boron incorporation from defects in the support to the palladium subsurface, creating the desired isolated ensembles determining the selectivity. This practical approach highlights the unexplored potential of using tailored carriers for catalyst design. Abstract : Defects in porous boron nitride enable the incorporation of boron atoms to the lattice of supported palladium nanoparticles, creating spatially isolated ensembles of metallic character. Evaluation in the continuous semi‐hydrogenation of 1‐hexyne demonstrates that the modification induced by the carrier can yield unparalleled performance compared to state‐of‐the‐catalysts without the need for introducing further additives.